Is Corporate Social Responsibility and Firm Performance Moderated by Employees’ Individual Beliefs of Social Responsibility? - Saeidi, Sayedeh Parastoo; Mohd Shahwahid Haji Othman; Sayyedeh Parisa Saeidi; Parvaneh Saeidi (European Journal of Multidisciplinary Studies, 2017)
Many studies reported in the literature to date, have looked into the benefits of CSR, specifically focusing more on the financial aspect but relatively less on employees. Therefore, CSR research with regards to employees’ perspective can be considered as almost an uncharted path. Accordingly, our key research objective in this study is to find out whether employees’ individual perception and beliefs of social responsibility can play a moderating role on CSR-sales growth relationship. A total of 328 SMEs in consumer product and manufacturing industry from Tehran (capital city of Iran) were engaged in this study. Structural equation methodology based on AMOS path modeling was applied to test all hypotheses of the study. The first part of the results reveals that the CSR has a positive but weak effect on sales growth as firm performance measure. The second part discloses that the positive effect of CSR on sales growth is improved when moderator (high level of employees’ individual beliefs of social responsibility) is included.